2016
DOI: 10.1016/j.celrep.2016.03.092
|View full text |Cite
|
Sign up to set email alerts
|

Independent Regulation of Type VI Secretion in Vibrio cholerae by TfoX and TfoY

Abstract: SummaryType VI secretion systems (T6SSs) are nanomachines used for interbacterial killing and intoxication of eukaryotes. Although Vibrio cholerae is a model organism for structural studies on T6SSs, the underlying regulatory network is less understood. A recent study showed that the T6SS is part of the natural competence regulon in V. cholerae and is activated by the regulator TfoX. Here, we identify the TfoX homolog TfoY as a second activator of the T6SS. Importantly, despite inducing the same T6SS core mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
131
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(143 citation statements)
references
References 40 publications
11
131
1
Order By: Relevance
“…The recently identified third auxiliary cluster is predicted to encode for one PAAR motif protein (VCA0284) and a unique effector-immunity pair (VCA0285-86) [22,43]. In addition to the promoters found upstream of each operon, internal promoter activity has been identified within the large cluster and auxiliary clusters 1 and 2 that lie just upstream of the immunity genes [41,45]. The transcriptional regulators that drive expression from these internal promoters are not well understood; however it has been hypothesized that they may allow immunity proteins to be constitutively expressed, thus ensuring protection from neighboring kin cells even in the absence of an active T6SS [41].…”
Section: T6ss Genetic Organization and Regulationmentioning
confidence: 99%
“…The recently identified third auxiliary cluster is predicted to encode for one PAAR motif protein (VCA0284) and a unique effector-immunity pair (VCA0285-86) [22,43]. In addition to the promoters found upstream of each operon, internal promoter activity has been identified within the large cluster and auxiliary clusters 1 and 2 that lie just upstream of the immunity genes [41,45]. The transcriptional regulators that drive expression from these internal promoters are not well understood; however it has been hypothesized that they may allow immunity proteins to be constitutively expressed, thus ensuring protection from neighboring kin cells even in the absence of an active T6SS [41].…”
Section: T6ss Genetic Organization and Regulationmentioning
confidence: 99%
“…It is well established that chitin-degradation products play a key role in the establishment of the V. fischeri-squid symbiosis (16). As chitin-degradation products induce the T6SS in V. cholerae (12,13), it is conceivable that the same holds true for the T6SS1 of V. fischeri. Indeed, chitin-induced T6SS1 production could occur within the chitin-rich mucus matrix that coats the ciliated surface of the squid's light organ, which might foster competitor exclusion upon initial association with the host.…”
mentioning
confidence: 89%
“…1), consistent with the fact that many Vibrio species interact with and feed on natural chitinous surfaces. The authors further deciphered a regulatory link between T6SS induction and natural competence for transformation and demonstrated that T6SS-mediated interbacterial competition can be used by V. cholerae to acquire DNA from killed prey, thereby fostering horizontal gene transfer (12,13). These examples highlight the need to move research toward more realistic conditions that mimic the natural habitats of the bacteria under investigation.…”
mentioning
confidence: 99%
“…In contrast, the majority of environmental, but not clinical, isolates constitutively killed Escherichia coli prey. Because different regulatory schemes control the phenotypes tested (11, 12), we sought to better understand the genetics that underlie these diverse V. cholerae phenotypes by characterizing whole-genome sequences of 23 environmental and three clinical isolates from Bernardy et al…”
Section: Genome Announcementmentioning
confidence: 99%